FORMATION OF INFORMATION COMPETENCE OF THE FUTURE PSYCHOLOGIST - Лаврухіна, Т. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the articles generalized theoretical positions are in relation to essence of concept «the Informative competence», as sense of locality of personality in the stream of information, as ability to work with the different types of information, find and take away necessary material, classify it, summarize, critically to him to belong, on the basis of the obtained knowledge to settle any informative problem related to professional activity. Certain and the analysed structural components of informative competence of practical psychologist, sent to the increase of professional competence